STUDY ON DETERMINING THE LOCATION FOR THE DEVELOPMENT OF A TYPE A PASSENGER TERMINAL IN TANJUNG SELOR, NORTH KALIMANTAN PROVINCE - Rio Riswanda; Alfa Narendra (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Bulungan Regency, with its capital in Tanjung Selor, has a strategic position as the administrative center of North Kalimantan Province and the location of the planned Independent New City (KBM). The increased status of this region has triggered high community mobility, which requires the availability of representative transportation infrastructure. Currently, Tanjung Selor does not have a Type A Passenger Terminal, so transportation operations are not yet optimal and integrated. This study aims to determine the most optimal location for terminal construction and analyze its potential for development as an integrated area. The research method uses a mixed method approach. Location priority is determined using the Analytical Hierarchy Process (AHP) method based on accessibility, spatial planning, technical, economic, and environmental criteria. Furthermore, a spatial analysis based on the Transit Oriented Development (TOD) concept was conducted at the selected locations to measure intermodal integration and accessibility. The AHP analysis results showed the following priority order: (1) Point 4 in Tanjung Selor Hilir (former PU workshop) as the top priority with a cumulative score of 3.00, (2) Point 2 on Jl. Sengkawit with a score of 2.90, and (3) Point 1 on Jl. Sabanar Lama with a score of 2.69. Further TOD analysis shows that Point 4 in Tanjung Selor Hilir has high feasibility as an integrated transportation hub, with a connectivity distance of 3 km to Tanjung Harapan Airport and 6 km to Kayan II Port. Buffering analysis shows that a 500-meter walking radius from this point can reach office and residential centers, supported by the presence of 84 hectares of green open space (RTH) that supports the principle of sustainable development.